Efeito das toxinas urêmicas guanidina e ácido guanidinoácetico sobre o metabolismo oxidativo e apoptose em neutrófilos de cães - Pereira, Priscila Preve [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
It has been recently reported that in canine chronic renal failure (CRF) there occurs oxidative stress, and that neutrophil dysfunction is associated with the increase of apoptosis. Among the many uremic toxins found in higher concentrations due to CRF, there is evidence - in humans - that guanidines inhibit the oxidative metabolism of neutrophils, affecting their bactericidal function. In this study, a systematic review of the relationship between guanidine compounds and neutrophils in dogs was undertaken. It was found that the literature on this subject is scarce and conflicting, which prompted this investigation of the relationship between the plasmatic concentration of guanidine, the production of superoxide, and the apoptosis of neutrophils in dogs with CRF. Morever, the effect of the isolated compound guanidine acetic acid (GAA) on the production of superoxide and on neutrophil apoptosis in healthy dogs was investigated in vitro. It was possible to verify that the large increase of plasmatic guanidine observed in dogs with CRF is not associated with the altered oxidative metabolism and the apoptosis of the neutrophils. The GAA inhibited the oxidative metabolism of the neutrophils in healthy dogs without affecting the viability of these cells
Keywords: Uremia; Apoptose; Leucócitos; Cão; Metabolismo; Guanidina; respiratory burst